An examination of the social background of students in Irish universities - Nevin, Monica (Statistical and Social Inquiry Society of Ireland, 1968)
It is obvious that to classify anything you must have some standard of selection. When we come to human society we find that the members of a society, could be classified in an indefinite number of ways depending on the objects or attributes chosen as criteria. Both objective and subjective criteria are relevant: first objective criteria: sex, income, occupation, education, material possessions, etc., etc.; secondly: subjective criteria: "I am working class" etc., or self-assessed status, participation in certain social activities and relationships.
Read before the Society, 10 May 1968
Keywords: University education; Social background of university students; Inequality in education; 314.15